Climate change impacts on plant diseases and crop protection - Lacroix, Octave (Hmeljarski bilten, 2025)
Climate change is considered one of the greatest threats to agriculture, resulting in significant yield losses and the loss of arable land due to various factors, ranging from unfavorable climate conditions to soil fertility issues. One significant aspect of climate change affecting crops is the development of diseases. The main factors of climate change affecting agriculture are the increase in temperature and CO2 levels, as well as the alteration of precipitation regimes, which can lead to extreme weather events such as droughts and floods. These factors considerably affect pathogens' expression of disease in hosts, as well as their spatial and temporal distribution and life cycle limiting factors, which are now changing. Early studies show an increase in the severity and occurrence of diseases caused by pathogens in crops, a reduction in plant defense mechanisms, the emergence of new, adapted, and more aggressive pathogen strains, and a wider and faster expansion of pathogens. However, the efficacy of plant protection products is also reduced. However, each pathosystem is affected differently by climate change, and mitigating effects must be studied independently.
Keywords: fitopatologija; food security; global warming; globalno segrevanje; plant pathogens; plant pathology; prehranska varnost; rastlinski patogeni